Digital Ektypon: Using an RTI Dome for Digitizing Squeezes and Epigraphic Research - Ilias N. Gotsikas; Yannis Z. Tzifopoulos; Pericles A. Mitkas (IEEE Access)
This paper unravels the transformative potential of Reflectance Transformation Imaging (RTI) in the context of epigraphy, shedding light on previously concealed dimensions of ancient artifacts, while introducing this technology to the digitization of epigraphic squeezes. Facing challenges related to the delicate nature of these paper-based copies and their preservation needs, this work developed a novel workflow incorporating RTI by a specially crafted Dome engineered for this purpose. The construction, calibration, and operational aspects of this dome are presented in this paper using as a case study the “Palaikastron Hymn” squeeze. The resulting high-resolution Polynomial Texture Maps enable the detailed exploration of inscriptions, enhancing the visibility of faded and subtle relief previously unseen. This research not only pioneers the application of RTI in the realm of epigraphy but also underscores its potential benefits in preserving and comprehensively studying fragile cultural artifacts, while enhancing scholarly analysis and understanding. In a world where the past meets cutting-edge technology, this research augments the arsenal of tools for digital humanities, ensuring that the legacy of ancient inscriptions is studied, preserved, and appreciated by scholars and enthusiasts alike.